In operando charge transport imaging of atomically thin dopant nanostructures in silicon. Issue 17 (13th April 2022) - Kölker, Alexander; Gramse, Georg; Stock, Taylor J. Z.; Aeppli, Gabriel; Curson, Neil J.
Abstract : We exploit the full capabilities of electrical scanning probe microscopy (e-SPM) to inspect the charge carrier transport of an electrically contacted, buried phosphorus, 2D nanowire (P-wire) in operando. Abstract : Novel approaches to materials design, fabrication processes and device architectures have accelerated next-generation electronics component production, pushing device dimensions down to the nano- and atomic-scale. For device metrology methods to keep up with these developments, they should not only measure the relevant electrical parameters at these length-scales, but ideally do so during active operation of the device. Here, we demonstrate such a capability using the full functionality of an advanced scanning microwave/scanning capacitance/kelvin probe atomic force microscope to inspect the charge transport and performance of an atomically thin buried phosphorus wire device during electrical operation. By interrogation of the contact potential, carrier density and transport properties, we demonstrate the capability to distinguish between the different material components and device imperfections, and assess their contributions to the overall electric characteristics of the device in operando . Our experimental methodology will facilitate rapid feedback for the fabrication of patterned nanoscale dopant device components in silicon, now important for the emerging field of silicon quantum information technology. More generally, the versatile setup, with its advanced inspection capabilities, delivers a comprehensive method to determine the performance of nanoscale devices while they function, in a broad range of material systems.